PERANCANGAN READY-TO-WEAR UNTUK ANAK MUDA DENGAN BATIK PHOENIX KONTEMPORER PADA BRAND DRL (Moda : The Fashion Journal, 2022)
Batik is an Indonesian cultural heritage that has been recognized by UNESCO, batik in Indonesia has diverse motives and in each region has unique and different characteristics. The batik technique was originally handmade batik which was processed using canting and wax, as well as the process of using human labor, because of that it has more value and high price. But as the times evolve, various batik techniques emerge which process is faster, by using mechanical power so that it can be sold at a cheap price, the technique is of various kinds, one of which is stamp batik. This modern batik technique makes it possible to make motifs that are more modern and most commonly found on the market. Therefore, batik also requires the development of motifs so that it can compete with other batik techniques, moreover handmade batik is an original technique that must be preserved. Batik in the past was quite in demand in the field of fashion, but with the rapid development of the world with the influence of technology and culture from outside which also influenced fashion trends. Because of that batik began to lag behind, because it was considered too formal, old-fashioned, so that young people are less interested. Therefore the development of batik needs to be done so that it can continue to compete with other fashion trends, and so batik is not forgotten because it is inferior to other developing trends. Therefore the research was conducted with interview techniques and surveys of experts and extreme users, and it is known that batik can develop through motifs and designs. And from the results of research on the target market can also be known colors and designs that are preferred. From these results obtained ideas to design batik with contemporary motif designs, as well as modern styles that follow fashion trends.